Agave biotechnology: an overview. (24th July 2014) - Nava-Cruz, Naivy Y.; Medina-Morales, Miguel A.; Martinez, José L.; Rodriguez, R.; Aguilar, Cristóbal N.
Abstract: Agaves are plants of importance both in Mexican culture and economy and in other Latin-American countries. Mexico is reported to be the place of Agave origin, where today, scientists are looking for different industrial applications without compromising its sustainability and preserving the environment. To make it possible, a deep knowledge of all aspects involved in production process, agro-ecological management and plant biochemistry and physiology is required. Agave biotechnology research has been focusing on bio-fuels, beverages, foods, fibers, saponins among others. In this review, we present the advances and challenges of Agave biotechnology.